An injectable liposome for sustained release of icariin to the treatment of acute blunt muscle injury. (22nd June 2020) - Wang, Jinwu; Zhu, Gaosheng; Wang, Xingyu; Cai, Jie; Xie, Linzhen; Zheng, Wenhao; Feng, Yongzeng; Guo, Qiang; Chen, Hua; Cai, Leyi
Abstract: Objectives: Icariin, extracted from Epimedium, is a kind of flavonoid and possesses osteogenesis and antioxidant. This study aimed to evaluate the therapeutic effects of icariin liposome on acute blunt skeletal muscle injury in rats. Methods: Icariin liposome was prepared by the thin-film dispersion method. After muscle injury, the corresponding treatment measures were given every day for two weeks. Recovery and mechanism of muscle injury were evaluated by QRT-PCR, HE, immunohistochemistry, malondialdehyde, superoxide dismutase and serological tests. Key findings: The particle size, polydispersity index, zeta potential, encapsulation efficiency and drug loading of icariin liposomes were 171.37 ± 38.23 nm, 0.27 ± 0.01, −5.59 ± 1.36 mV, 78.15 ± 2.04% and 15.62%, respectively. The QRT-PCR showed that icariin liposome significantly promoted the expression of MHCIIB and vimentin. Through HE, immunohistochemistry, ELISA and serological tests, we found that icariin liposome effectively promoted desmin expression, reduced collagen I expression and inhibited the production of pro-inflammatory factors, including TNF-α and IL-6. Icariin liposome therapy significantly reduced the level of malondialdehyde and increased the activity of superoxide dismutase. Conclusions: Icariin liposome has excellent therapeutic effects on acute blunt muscle injury in rats by improving immunity, repairing cytoskeleton and cellular integrity, anti-inflammation, anti-fibrosis and antioxidant stress.